Ministerial Decree No. 150/2016 Regarding the Establishment of a Committee for Deciding on the Requests for the exception from the Prescribed Percentage of the Employment of Foreign Labor against the Egyptian Labor, and the Determination of the Responsibilities thereof = قرار وزاري رقم 150 لسنة 2016 بشأن تشكيل لجنة للبت في طلبات الاستثناء من النسبة المقررة لاستخدام العمالة الأجنبية مقابل العمالة المصرية وتحديد اختصاصتها - Egypt; The middle east library for economic services, translator. (2025)
ministry of manpower Decree No. 150 of the year 2016 Regarding the Establishment of a Committee for Deciding on the Requests for the exception from the Prescribed Percentage of the Employment of Foreign Labor against the Egyptian Labor, and the Determination of the Responsibilities thereof وزارة القوى العاملة قرار رقم 150 لسنة 2016 بشأن تشكيل لجنة للبت فى طلبات الاستثناء من النسبة المقررة لاستخدام العمالة الاجنبية مقابل العمالة المصرية، وتحديد اختصاصاتها